Improving the Mentoring Process for Social Entrepreneurship in Portugal: A Qualitative Study. Issue 3 (2nd September 2019) - Thomaz, Inês Fernandes; Catalão-Lopes, Margarida
Abstract: Social entrepreneurship aims to find innovative and self-sustainable solutions to social problems. The mentoring process is a crucial component, yet relatively less addressed, of social entrepreneurship. This paper analyses the different perspectives towards mentoring of the main actors in the social entrepreneurship ecosystem in Portugal, making use of interviews and focus groups and qualitative data analysis. The major challenges faced are identified and discussed. Recommendations to improve the mentoring process to new social entrepreneurs are withdrawn. Study findings are of value to all entities involved in the ecosystem.